Acceptability of 11 fortified balanced energy‐protein supplements for pregnant women in Nepal. Issue 3 (9th March 2022) - Lama, Tsering P.; Khatry, Subarna K.; Isanaka, Sheila; Moore, Katie; Jones, Leslie; Bedford, Juliet; Katz, Joanne; de Pee, Saskia; LeClerq, Steven C.; Tielsch, James M.
Abstract: Evidence suggests that multiple micronutrient and balanced energy protein (BEP) supplementation during pregnancy can decrease the risk of stillbirth and small‐for‐gestational‐age births and increase birth weight. We conducted a mixed‐methods formative research study to identify the most acceptable among a range of 11 candidates fortified BEP supplements for use in pregnancy and lactation in a rural district in Nepal. Forty pregnant women aged 15–40 years participated in a test meal tasting of 11 different sweet and savoury candidate BEP supplements. Each participant rated the products on organoleptic properties using a 7‐point hedonic scale (1 = Dislike it very much to 7 = Like it very much), ranked her 'top 3' most liked supplements, and subsequently discussed each product with peers in focus group discussions (FGDs). Five supplements (sweet lipid‐based nutrient supplement (LNS), savoury LNS, sweet vanilla biscuits, vanilla instant drinks and seasoned pillows) achieved the maximum overall median hedonic score of 7, with sweet LNS and seasoned pillows ranking as the top 2. This was consistent with the assessments in FGDs. Women in the FGDs expressed dislike of the smell and taste of the cocoa drink, savoury masala bar, sweet mango bar and savoury curry biscuit, which was consistent with the hedonic scale scores. This study provides valuable insights into our understanding of women's acceptance of different BEP supplements during pregnancy in rural Nepal and has helped identify the two most accepted BEP supplements to be used in a two‐month home trial to assess utilisation and compliance in this setting. Key messages: Understanding the acceptability of balanced energy protein supplements by pregnant women along with the potential facilitators and barriers to their use is vital to ensure regular consumption and compliance. Pregnant women in rural Nepal liked both the sweet and savoury products and suggested having the option to choose from more than one type of product would facilitate its daily consumption throughout pregnancy. Concerns regarding the cost of the supplements, strong aversion to smell/taste of certain supplements, and the inability to eat the supplement in private were some of the deterrents for possibly not being able to eat the supplement daily Abstract :